(untitled) (AYUSHDHARA, 2019)
Tuttha is mineral containing copper and sulphur, easily available and is well known for its medicinal use since ancient time. In modern medicine the use of Tuttha (copper sulphate) is much used as topical applications where as in Rasashastra Tuttha was used internally as well as externally therapeutically, many external applications were told in classical texts. So it is used for medicinal purpose and various Shodhana processes are adopted, which render Tuttha into the therapeutic form and free from the side effects. Presently Tutthadrava is prepared, marketed and practiced inspite of being explained as effective remedy for various disorders. In this study Tutthadrava was prepared by using Shodhit Tuttha. Three samples of Tuttha were collected from various places i.e., A1- market, A2- market, A3- market. All three samples were comparatively examined for their Grahya lakshanas. Comparative pharmaceutical study of Tuttha Shodhana and Tutthadrava Nirman and analytical study of Shodhit Tuttha and Tutthadrava was carried out. All the five Shodhit tuttha samples were subjected to analytical study in laboratory as pH, Total ash, Acid insoluble ash, Water insoluble Ash, Loss on drying at 105o c, Colour, Odour, Assay of element as Cu, Fe, S. was done and X-RD.